Determination of the causes of delays leading to poor operating room efficiency in a tertiary hospital in Pasig City - Aspi, Maria Teresita B.
Operating room efficiency may be defined in terms of lag times and operating room utilization. Determination of the present level of operating room efficiency, and identification of the modifiable factors contributing to delays enable the hospital to avoid wastage of resources, increase the number of surgeries per day, and improve OR revenue. A cross-sectional study employing a retrospective records review of all elective surgical cases from June 2023 to June 2024 at a tertiary hospital in Pasig City was carried out to describe the status of its OR efficiency, identify the direct causes of delays, and predict the change in the number of patients served and OR income if utilization rates improve. The means of the arrival of first case lag time, anesthesia induction lag time and turnover time did not reach target, while the means of the procedure lag time, trans-out lag time and utilization rate were optimal. Among the different causes, those related to the surgeon predominated. The relationship between the change in utilization rate and change in the number of patients served was not significant. Likewise, there was no significant relationship between the change in the number of patients served and the change in gross income. Since the utilization rate of the functioning operating rooms was already ideal, the current number of functioning operating rooms may no longer be enough to address the existing backlog of cases. Increasing the number of functioning operating rooms may be considered.